2020
DOI: 10.5152/iao.2020.7709
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Otitis Externa: Causes for Various Treatment Responses

Abstract: The Journal of International Advanced Otology (J Int Adv Otol) is an international, peer reviewed, open access publication that is fully sponsored and owned by the European Academy of Otology and Neurotology and the Politzer Society. The journal is published triannually in April, August, and December and its publication language is English. The scope of the Journal is limited with otology, neurotology, audiology (excluding linguistics) and skull base medicine. The Journal of International Advanced Otology aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 0 publications
2
23
1
5
Order By: Relevance
“… 16 17 Previous studies have reported isolated VII or VIII CN palsy which may be because of inclusion of patients with malignant otitis externa. 18 On the contrary, in our cohort, majority had atypical SBO (80%) with no obvious clinical foci of infection elsewhere. Venous thrombosis is said to be more commonly associated with SBO, but we did not encounter any such patient.…”
Section: Discussioncontrasting
confidence: 56%
“… 16 17 Previous studies have reported isolated VII or VIII CN palsy which may be because of inclusion of patients with malignant otitis externa. 18 On the contrary, in our cohort, majority had atypical SBO (80%) with no obvious clinical foci of infection elsewhere. Venous thrombosis is said to be more commonly associated with SBO, but we did not encounter any such patient.…”
Section: Discussioncontrasting
confidence: 56%
“…The agents are bacteria such as methicillin-resistant Staphylococcus aureus (MRSA), Klebsiella and Proteus mirabilis or fungal agents such as Aspergillus and Candida . However, Pseudomonas aeruginosa is the leading pathogen especially in immunocompromised patients with comorbidities such as diabetes, HIV and hematological diseases 5 , 10 . The most common microorganism in the culture samples taken from the external auditory canal of the patients was Pseudomonas aeruginosa in accordance with literature 10 , 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the best imaging modality for diagnosing and assessing the treatment response in MOE has been a point of concern regarding the accuracy and cost-effectiveness 5 .…”
Section: Introductionmentioning
confidence: 99%
“…En pacientes con factores predisponentes como la diabetes descompensada o inmunosupresión por VIH, la otitis externa puede presentarse más agresivamente, denominándose otitis externa maligna 45,46 . Esta es una infección grave causada principalmente por Pseudomona aeruginosa, que puede extenderse al hueso temporal cortical, pudiendo afectar la apófisis mastoidea, el ápex petroso y causar osteomielitis de base de cráneo.…”
Section: Otitis Externaunclassified
“…Esta es una infección grave causada principalmente por Pseudomona aeruginosa, que puede extenderse al hueso temporal cortical, pudiendo afectar la apófisis mastoidea, el ápex petroso y causar osteomielitis de base de cráneo. Se presenta con otalgia intensa, que no cede con la analgesia, otorrea, generalmente sin fiebre, y puede evolucionar con compromiso de pares craneanos 46 . El abordaje quirúrgico con debridamiento de los tejidos infectados es parte importante de la terapia y deben tomarse tinciones como cultivos para identificación microbiológica y la mejor elección de los antibióticos.…”
Section: Otitis Externaunclassified